A Qualitative Study of Mentally Ill Women Who Commit Filicide in Gauteng, South Africa - Moodley, Sanushka; Subramaney, Ugasvaree; Hoffman, Daniel (Frontiers in Psychiatry, 2019)
Introduction Filicide is the deliberate act of a parent killing his/her own child and a major contributor to child homicide rates. In order to prevent future homicides of this nature and aid in the rehabilitation of those mentally ill women who perpetrate these crimes, it is important to gain a better understanding of the dynamics that may result in filicide and the association of the mental illness with filicide. It is also important to explore how the rehabilitation processes are experienced and the impact they have had. The purpose of this study was to examine the perceptions of women regarding their offences and their perceptions about their treatment and rehabilitation in a South African context. Method This was a qualitative study which followed a naturalistic paradigm. The data from the semi-structured interviews conducted were analyzed using thematic analysis. The use of subjective experiences and descriptions by the participants aimed to give a representation of the participants’ lived experience. This allowed the authors to explore the emerging themes, sub-themes and concepts and organize the most replicated information into a hierarchical assessment. The semi-structured interviews were conducted with 7 filicidal women with mental illness between July 2016 and April 2017 at Sterkfontein Hospital, Gauteng, South Africa. Results Most filicidal mothers were psychotic at the time of the offence, and perceived trauma and regret for their offences. Support from the community as well as empathy and unconditional positive regard from the staff, notably psychologists and occupational therapists were overwhelmingly present. Conclusion Filicide is tragic and largely understudied, particularly from the perpetrator’s perspective. When perpetrators are mentally ill, rehabilitation within a non-judgmental and empathetic environment is necessary.